Language practice for advanced : - Vince, Michael (MacMillan, 2014)
Offers an in-depth, detailed approach to English grammar and vocabulary, providing clear grammar explanations, plenty of practice and regular review units. This title includes an accompanying MPO that provides extra practice. It is suitable for students preparing for the First exam, and can be used in class or for self-study. It comes 'With Key'.